Spread of the Fosfomycin resistance fosA3 gene via the IS26 mobile element between plasmids and the chromosome of carbapenem-resistant Escherichia coli in China - Ying Zhang; Chuanxin Yang; Jiayao Yao; Longjie Zhou; Xiaofan Zhang; Huan Wang; Lijuan Liu; Yuexing Tu; Xi Li (Journal of Global Antimicrobial Resistance)
Objective: This study investigated fosA3-positive strains selected from carbapenem-resistant Escherichia coli (CREC) and further characterized them through genomic and phenotypic analyses. Methods: fosA3-positive CREC strains were subjected to agar dilution. Whole-genome sequencing (WGS) was used to identify molecular mechanisms of fosfomycin resistance and to investigate plasmid structure characteristics through comparative analysis. Conjugative transfer experiments were used to evaluate plasmid transfer ability, followed by plasmid stability assessment. Growth rate analysis evaluated the fitness costs of transconjugants. Phylogenetic analysis was performed on fosA3-positive CREC strains. Furthermore, analysis of fos genes carrying E. coli sequence types (STs) from the NCBI database explored the evolution and spread of fosfomycin resistance. Results: Between 2016 and 2023, a total of 11.23% CREC strains (10/89) carrying fosA3 were collected from a hospital for further analysis. These ten fosA3-positive strains were also resistant to fluoroquinolones and ceftazidime-avibactam. The fosA3 gene was located within a similar genetic background (IS26-fosA3–1811bp-IS26) on plasmids or chromosomes. The fosA3-carrying IncFII(pHN7A8)-IncX3 cointegrate plasmid pEC00–2–145k was transferable, with fitness cost of 20% to host. Furthermore, three of ten fosA3-positive CREC strains belonged to ST156. Analysis of fos genes carrying E. coli strains from China in the NCBI database identified ST156 (5.39%, 147/2,725) and ST167 (5.21%, 142/2,725) as predominant STs. Conclusions: This study revealed fosA3 in CREC strains was associated with IS26 and spreads fosfomycin resistance through horizontal transfer, occurring both on chromosomes and plasmids. The first fosA3-carrying cointegrate plasmid pHN7A8-IncX3-type in E. coli isolates was reported, highlighting a new route of fosfomycin resistance spread. Additionally, notable diversity of ST among fosA3-carrying E. coli strains highlights complexity of fosfomycin resistance dissemination and the importance of surveillance and control measures.